Experimental measurement of strain and stress state at the contacting helical gear pairs - Patil, S.S. (Elsevier B.V., 2016)
Contact stress evaluation in gears has been a complex area of research, due to its non-linear and non-uniform nature of stress distribution. The high contact stress on gears results in pitting and scuffing, which leads to tooth failure. Furthermore the effects of friction on gear contacts make the problem more complicated. Hence, in this paper, attempt has been made to study contact stress in gears. The experimental testing and analysis of the helical gear was carried out using Gear Dynamic Stress Test Rig (GDSTR). GDSTR is a newly designed test rig to compute the contact stresses on the gear pair contact, under real gear conditions. GDSTR uses the strain gauge and carbon slip rings to measure the surface contact stresses at the contacting points of a meshed gears. The experimental analysis showed promising results which have been verified by the finite element frictional contact analysis. The experimental testing was carried out on 5° and 25° helical gear pairs. Helical gear models with the same specifications and for different frictional coefficient conditions were also generated using FE modelling. The frictional contact stress analysis using FEM has been used for comparison with the experimental results. © 2016 Elsevier Ltd.